Ameliorative role of neem (Azadiracta indica) leaves ethanolic extract on testicular injury of neonatally diabetic rats induced by streptozotocin. Issue 1 (1st January 2020) - El-Beltagy, Abd El-Fattah B. M.; Abou El-Naga, Amoura M.; El-Habibi, El-Sayed M.; Shams, Sara El-Said M.
ABSTRACT: One of diabetes mellitus complications is the disturbance in the structure and functions of male reproductive organs. The present study aimed to evaluate the ameliorative role of Azadiracta indica leaves extract against adverse effects of diabetes on the structure and function of the testicular tissue of rats neonatally induced by streptozotocin. Twenty-four male Albino rats at 6 weeks old were used in the present study and divided into four groups (n=6). Group 1: control group, group 2: neem leaves extract supplemented group. Group 3: diabetic group that received a single I.P dose of Streptozotocin and group 4: diabetic group supplemented with neem leaves extract. The obtained results revealed significant decreased levels of testicular antioxidants, serum testesterone and significant increased levels of serum cholesterol, triglycerides, and low density lipoprotein but a remarkable decrease in high density lipoprotein in diabetic rats. Also, the testicular tissues of diabetic rats displayed several histological and ultrastructural changes especially in the spermatogenic and interstitial cells as well as overexpression of COX-2 protein if compared with control. Post-supplementation of neem leaves extract to STZ- induced diabetic rats, revealedremarkable amelioration in most of disrupted estimated parameters.